Genomewide Approach Validates Thiopurine Methyltransferase Activity Is a Monogenic Pharmacogenomic Trait. Issue 3 (18th November 2016) - Liu, C; Yang, W; Pei, D; Cheng, C; Smith, C; Landier, W; Hageman, L; Chen, Y; Yang, JJ; Crews, KR; Kornegay, N; Karol, SE; et al.
Abstract : We performed a genomewide association study (GWAS) of primary erythrocyte thiopurine S‐methyltransferase ( TPMT ) activity in children with leukemia ( n = 1, 026). Adjusting for age and ancestry, TPMT was the only gene that reached genomewide significance (top hit rs1142345 or 719A>G; P = 8.6 × 10 ‐61 ). Additional genetic variants (in addition to the three single‐nucleotide polymorphisms [SNPs], rs1800462, rs1800460, and rs1142345, defining TPMT clinical genotype) did not significantly improve classification accuracy for TPMT phenotype. Clinical mercaptopurine tolerability in 839 patients was related to TPMT clinical genotype ( P = 2.4 × 10 ‐11 ). Using 177 lymphoblastoid cell lines (LCLs), there were 251 SNPs ranked higher than the top TPMT SNP (rs1142345; P = 6.8 × 10 ‐5 ), revealing a limitation of LCLs for pharmacogenomic discovery. In a GWAS, TPMT activity in patients behaves as a monogenic trait, further bolstering the utility of TPMT genetic testing in the clinic.